To Be or Not to Be an Empathic EFL Teacher: A Correlational Analysis of Empathy and Classroom Management Orientations - Hassanpour Souderjani, Roya; Heidari Darani, Laya; Hosseinpour, Nafiseh (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This study examined Iranian EFL teacher’s empathy level and their classroom management orientations. Furthermore, the relationship between these two variables was probed. To this end, 245 male and female Iranian EFL teachers between 20 and 55 years old participated. Data were collected through classroom management and empathy questionnaires. Results indicated that the teachers had a relatively high level of empathy and they tended toward behavioral management orientation. In addition, the two variables were correlated. It is concluded that empathizing with students can make them feel more at ease and more relaxed, increasing their motivation for language learning. Moreover, behavior management acts as a pre-requisite for instructional management. The more teachers empathize with students, the more and the better control they have in their classroom management.